THE EXISTENCE OF THE SOROGAN METHOD IN THE 21ST CENTURY: ITS EFFECTIVENESS, ROLE, AND RELEVANCE IN MODERN EDUCATION - Mas'ud; Tamrin Subagyo; M. Fahmi Arifin (STAI Ma'had Aly Al-Hikam Malang, 2025)
The Sorogan method is a traditional learning approach that remains popular and widely implemented in both formal and non-formal educational institutions. Its enduring existence over time demonstrates the uniqueness of this method in terms of adaptability and resilience to changing eras. This study aims to describe the findings of a systematic literature review (SLR) concerning the effectiveness and relevance of the Sorogan method in the context of contemporary Islamic education, explore its role in learning, and provide recommendations for improving education quality. The research employed the SLR method, utilizing data sources from accredited national and international journal articles published within the last ten years, as well as books, academic manuscripts, and other relevant references. The study was conducted systematically through six stages: (1) topic determination, (2) literature search, (3) article selection and reduction, (4) data presentation, (5) analysis and discussion, and (6) conclusion drawing. The results indicate that the Sorogan method remains effective for modern learning when innovation and adjustments are made in line with current developments. Its relevance is still strong in addressing contemporary educational needs, particularly in enhancing learning effectiveness, motivating students, and strengthening the teacher-student relationship. Recommendations to improve the effectiveness of the Sorogan method include: (1) considering students' readiness for learning, (2) integrating it with other relevant teaching methods, (3) utilizing information and communication technology, and (4) encouraging teachers to actively adapt instruction to students' needs. Keywords: Sorogan Method, Effectiveness and Role, Relevance in Modern Education. Abstrak Metode Sorogan merupakan pendekatan pembelajaran tradisional yang tetap populer dan banyak diterapkan di lembaga pendidikan baik formal maupun nonformal. Eksistensinya yang bertahan dari masa ke masa menunjukkan keistimewaan metode ini baik dari segi adaptabilitas maupun pamornya terhadap perubahan zaman. Penelitian ini bertujuan untuk mendeskripsikan hasil kajian systematic literature review (SLR) terkait efektivitas dan relevansi metode Sorogan dalam konteks pendidikan Islam kontemporer, mengeksplorasi perannya dalam pembelajaran, serta memberikan rekomendasi untuk peningkatan mutu pendidikan. Metode penelitian yang digunakan adalah SLR dengan sumber data berupa artikel jurnal nasional dan internasional terakreditasi dalam sepuluh tahun terakhir, serta buku, naskah akademik, dan sumber relevan lainnya. Penelitian ini dilakukan secara sistematis melalui enam tahapan; 1) penentuan topik, 2) pencarian literatur, 3) seleksi dan reduksi artikel, 4) penyajian data, 5) analisis dan pembahasan, dan (6) penarikan kesimpulan. Hasil penelitian menunjukkan metode Sorogan masih cukup efektif diterapkan dalam pembelajaran modern masa kini dengan diberikan inovasi dan penyesuaian yang berorientasi pada perklembangan zaman. Relevansinya tetap kuat dengan kebutuhan pembelajaran masa kini, khususnya dalam meningkatkan efektivitas pembelajaran, memotivasi peserta didik, dan mempererat hubungan guru dengan siswa. Rekomendasi untuk meningkatkan efektivitas metode Sorogan meliputi: (1) perhatikan kesiapan belajar siswa dalam penerapan metode ini, (2) pengintegrasian dengan metode pembelajaran lain yang relevan, (3) pemanfaatan teknologi informasi dan komunikasi, serta (4) guru hendaknya berperan aktif dalam menyesuaikan pembelajaran dengan kebutuhan peserta didik. Kata Kunci: Metode Sorogan, Efektivitas dan Peran, Relevansi pada Pembelajaran Masa Kini